Pocket CLARITY enables distortion-mitigated cardiac microstructural tissue characterization of large-scale specimens - Kim, Joan J. H.; Parajuli, Shestruma; Sinha, Aman; Mahamdeh, Mohammed; van den Boomen, Maaike; Coll-Font, Jaume; Chen, Lily Shi; Fan, Yiling; Eder, Robert A.; Phipps, Kellie; Yuan, Shiaulou; Nguyen, Christopher (Frontiers in Cardiovascular Medicine, 2022)
Molecular phenotyping by imaging of intact tissues has been used to reveal 3D molecular and structural coherence in tissue samples using tissue clearing techniques. However, clearing and imaging of cardiac tissue remains challenging for large-scale (>100mm3) specimens due to sample distortion. Thus, directly assessing tissue microstructural geometric properties confounded by distortion such as cardiac helicity has been limited. To combat sample distortion, we developed a passive CLARITY technique (Pocket CLARITY) that utilizes a permeable cotton mesh pocket to encapsulate the sample to clear large-scale cardiac swine samples with minimal tissue deformation and protein loss. Combined with light sheet auto-fluorescent and scattering microscopy, Pocket CLARITY enabled the characterization of myocardial microstructural helicity of cardiac tissue from control, heart failure, and myocardial infarction in swine. Pocket CLARITY revealed with high fidelity that transmural microstructural helicity of the heart is significantly depressed in cardiovascular disease, thereby revealing new insights at the tissue level associated with impaired cardiac function.